Depression and Anxiety among Undergraduate Students in a Medical College of Rupandehi - Vaidya, Gemorina; Shrestha, Neelam; Dhungana, Manoj; Thapa, Namrata (Journal of Karnali Academy of Health Sciences, 2025)
Background: Depression and anxiety being the common health problems globally, are found highly prevalent among medical students. This study aimed to assess prevalence of depression and anxiety and its associated factors among undergraduate students.Methods: A descriptive cross-sectional study was conducted to assess depression and anxiety among undergraduate students of a medical college in Rupandehi using a convenience sampling technique. Self-administered questionnaire and DASS 21 scale were used to collect the data from date 20th August 2022- 20th August 2023 and data were analyzed by using descriptive and inferential statistics with Statistical Package for Social (SPSS) 20.Results: The findings of the study revealed that 33.2% of the respondents had depression and 50.4% had anxiety. There was statistically significant association between age, pressure from parents, year of study, medical condition and stage of course and depression. Similarly, age, year of study and stage of course were significantly associated with anxiety.Conclusion: Based on the study findings, it is concluded that one third of the respondents have depression and more than half of the respondents have anxiety. This study emphasizes on developing strategies to identify students at risk and implementing specific coping mechanisms-such as exercising, socializing, and healthy eating-while promoting health seeking behaviors through improved mental health literacy.